CI/CD Implementation Application Deployment Process Academic Information System (Case Study Of Paramadina University) - Rendy Indriyanto; Diki Gita Purnama (Jurnal Indonesia Sosial Teknologi, 2023)
This research discusses the implementation of Continuous Integration/Continuous Delivery (CI/CD) in the deployment process of the Academic Information System application at Paramadina University, where the application development process still uses manual methods. CI/CD is an approach in software development that enables development teams to automatically integrate code, run tests, and deploy applications periodically and continuously. The purpose of this research is to implement CI/CD in the deployment process of Academic Information System applications so that the development process becomes more effective and the quality of the resulting application is better and more adaptable to changes. The method used in this research is the qualitative method by conducting direct observation to collect data. The results of the research show that by implementing the stages of CI/CD, the application deployment process becomes more efficient and can provide a solution to the problems that arise in the previously conventional or manual application deployment process. The results of this research can serve as a guide for development teams and operations who want to adopt CI/CD in the application deployment process, as well as provide insights for researchers and practitioners to optimize the use of CI/CD in software development.